GPS guided reverse shoulder arthroplasty: : an anatomic dissection study - Colasanti, Giovanni Battista; Moreschini, Fabio; Cataldi, Carlo; Mondanelli, Nicola; Giannotti, Stefano (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: The reverse shoulder arthroplasty (RSA) has risen exponentially, this has entailed an increasing number of complications and reoperations. In RSA, loads are transferred directly to the glenoid component. As a result, failure of the glenoid component is one of the most common complications. CT 3D preoperative planning, patient-specific and the possibility of performing a more precise and controlled surgical gesture in the operating room are increasingly important. The use of the GPS navigation on CT 3D planning has proved to be useful above all in terms of accuracy, reliability and the possibility of reproducing the planned gesture preoperatively. Methods: This study analyzes the precision, safety, and reproducibility of the GPS system for the reverse shoulder prosthesis tested on 6 scapulohumeral cadaver specimens, subsequently subjected to anatomical dissection to verify the correct positioning of the glenoidcomponents and the percentage of appropriateness in the field of planning previously virtually assumed. Results: Postoperative macroscopic dissection revealed no central peg perforated or screws malpositioned, no leaking from the bone or injury to the adjacent neurovascular structures. The average length of the screws was 42 mm (range 36 mm to 46 mm) for the lower screw and 40 mm for the upper one (range 36 mm to 42 mm). Conclusions: This cadaver study has shown that GPS navigation offers greater efficiency in baseplate and screws placement and can avoid intra- and postoperative complications.